A Phenomenological Study of Educators’ Experience After a Year of the COVID-19 Pandemic - Annamalai, Nagaletchimee; Ab Rashid, Radzuwan; Saed, Hadeel; Al-Smadi, Omar Ali; Yassin, Baderaddin (Frontiers in Psychology, 2022)
This phenomenological study investigated educators’ lived experiences of teaching online in higher institutions in Malaysia. Data, which was generated through semi-structured interviews with 20 lecturers from three universities in the country, was analysed based on the thematic analysis approach guided by the Technological, Pedagogical, and Content Knowledge (TPACK)-self-efficacy framework. The findings revealed that after a year of teaching online, the potential of technology has been acknowledged by the educators after some trials and constraints were addressed. The domains related to Technology Content Knowledge (TCK), Technology Pedagogical Knowledge (TPK), and TPACK were evident in the findings. However, Pedagogical Content Knowledge (PCK) was not given emphasis, hence this manuscript argues that educators need to be constantly reminded of the significance of PCK. The findings discussed in this manuscript can be a helpful guide for educators when there is a need for them to teach online.